Large-scale turbulent driving regulates star formation in high-redshift gas-rich galaxies - II. Influence of the magnetic field and the turbulent compressive fraction - Brucy, Noé; Hennebelle, Patrick; Colman, Tine; Iteanu, Simon (Astronomy and astrophysics, 2023)
Context. The observed star formation rate (SFR) in galaxies is well below what it should be if gravitational collapse alone were at play. There is still no consensus about the main process that cause the regulation of the SFR. Aims. It has recently been shown that one candidate that might regulate star formation, the feedback from massive stars, is suitable only if the mean column density at the kiloparsec scale is lower than ≈20 M⊙ pc−2. On the other hand, intense large-scale turbulent driving might slow down star formation in high-density environments to values that are compatible with observations. In this work, we explore the effect of the nature and strength of the turbulent driving, as well as the effect of the magnetic field. Methods. We performed a large series of feedback-regulated numerical simulations of the interstellar medium in which bidimensional large-scale turbulent driving was also applied. We determined the driving intensity needed to reproduce the Schmidt-Kennicutt relation for several gas column densities, magnetization, and driving compressibility. Results. We confirm that in the absence of turbulent forcing and even with a substantial magnetic field, the SFR is too high, particularly at a high column density, compared to the Schmidt-Kennicutt relation. We find that the SFR outcome strongly depends on the initial magnetic field and on the compressibility of the turbulent driving. As a consequence, a higher magnetic field in high column density environment may lower the energy necessary to sustain a turbulence that is sufficiently intense to regulate star formation. Conclusions. Stellar feedback does not seem to be sufficient to regulate star formation in gas-rich galaxies where large-scale turbulent driving may be needed. The sources of this large-scale turbulence as well as its characteristics, such as its intensity, compressibility, and anisotropy, need to be understood and quantified.
Online veröffentlicht: 14. Juli 2023
Gesehen am 04.10.2023